Digital Technology in Road Freight Logistics for Global Supply Chains - Bryant H Susanto; Achmad Fauzi; Febrianty S Hendrawan; Frikma P Novbona; Ribka Alexandra; Muhammad D Habibi (Siber International Journal of Digital Business (SIJDB), 2025)
Digital transformation plays a crucial role in improving operational efficiency and transparency of road logistics services in global supply chains. Technological innovations such as the Internet of Things (IoT), artificial intelligence (AI), and intelligent transportation systems (ITS) have revolutionized logistics processes through real-time tracking, route optimization, predictive vehicle maintenance, and more accurate inventory management. However, the adoption of these technologies is uneven between developed and developing countries due to differences in infrastructure, regulations, and human resource skills. This study aims to analyze the role of technology in improving logistics efficiency, compare adoption rates across countries, and identify barriers and solutions to achieving an inclusive and sustainable digital transformation. Thus, this research contributes to the development of literature and policy practices that support a resilient, transparent, and environmentally friendly road logistics system.